1973
DOI: 10.1111/j.1476-5381.1973.tb08189.x
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of lithium and its effects on the distribution and excretion of other ions in the rat

Abstract: Summary In rats, lithium (ca 1 mEquiv/kg body weight) decreased brain sodium and magnesium, bone sodium and calcium and increased muscle calcium, plasma magnesium, urinary calcium and urine volume. Lithium was particularly concentrated in bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

1975
1975
1986
1986

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 25 publications
3
47
0
Order By: Relevance
“…In accord with other studies (Birch & Jenner, 1973;Neilson, 1964a, b) in both man and animals, plasma magnesium was elevated in all the rats given lithium for 14 days.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…In accord with other studies (Birch & Jenner, 1973;Neilson, 1964a, b) in both man and animals, plasma magnesium was elevated in all the rats given lithium for 14 days.…”
Section: Resultssupporting
confidence: 78%
“…Comparing the results of the present study with those of Birch & Jenner (1973), both show a decrease in brain magnesium proportionally depending on the dose of lithium, although in the latter case lithium was administered by intraperitoneal injection or in the drinking water. Also, Mellerup et al (1973) showed an increase in plasma magnesium after a single intraperitoneal injection of 900 ,umol of lithium chloride which is comparable to the increased magnesium level we obtained with a very different dosage and route of administration.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…' Gibbons (1960); Coppen & Shaw (1963); Hullin, Swinscoe, McDonald & Dransfield (1968) and Aronoff, Evens & Durrel (1971) reported that sodium excretion increased following the commencement of lithium treatment. Baer, Kassir & Fieve (1970) ;Ho, Gershon & Pinckney (1970); and Birch & Jenner (1973) found that chronic administration of lithium to rats results in a significant decrease in brain sodium concentration. An increase in serum magnesium concentration has also been observed to accompany treatment with lithium (Nielsen, 1964;Aronoff et al (1971); and Andreoli, Villani & Brambilla, 1972;Mellerup, Plenge & Rafaelsen, 1973;and Birch & Jenner, 1973).…”
Section: Introductionmentioning
confidence: 99%